Effectiveness of Therapeutic Community Rehabilitation Program for Drug Abuse in Social Institutions - Shaver, Scuka Rousseau; Forsyth, Oyelana; Meritus, Dionisius (Law and Economics, 2023)
This research conducts an evaluation of the Therapeutic Community (TC) Program implemented for residents grappling with drug abuse within social institutions. The study aims to assess the program's effectiveness, the impact on participants, and its implications for social institutions and the broader field of substance abuse treatment. Through a mixed-methods approach, the research scrutinizes quantitative data to measure changes in substance abuse levels, mental health, and readiness for reintegration, coupled with qualitative insights from participant experiences. The outcomes reveal significant reductions in substance abuse levels, improvements in mental health indicators, and positive behavioral changes among participants. The study highlights the pivotal role of peer support and community integration in residents' recovery journeys. The implications of the findings encompass enhanced recovery pathways for individuals, reinforcing the value of community support, while calling for sustained support mechanisms and comprehensive approaches within social institutions. This evaluation underscores the dynamic nature of substance abuse interventions and underscores the importance of continuous assessment, innovation, and adaptive strategies for improved rehabilitation initiatives.